Ethical Business Decision-Making in Organizations: A Theoretical Perspectives - Stephen Pembi; Bulus Kamna Ali (RSF Press, 2024)
Ethics issues are characterized by ambiguity and complexity, and they have high-stakes implications for both individuals and organizations. The study of business ethics focuses on identifying the moral standards of good and wrong that govern interactions between and within organisations. To sustain a competitive advantage in today's competitive market, business leaders must embrace ethical decision-making. Businesses that do not make ethical decisions, risk falling behind their market competitors. This research looks at ethical frameworks that can help managers distinguish between ethical and unethical business decisions. As it is a review of literature, the current study mainly depends on literature. Several theories, including utilitarianism, individualism, justice, and right theories, have been examined in this study to explain the underlying cognitive and behavioural processes governing ethical decision-making. The results show that while making moral decisions, managers need to be aware of the ethical ramifications of various issues and circumstances. As a result, managers should use ethical principles while making decisions, especially when it comes to stakeholders in a business. The findings of this study will assist other researchers in identifying comparable studies during the literature review stage of their research and will serve as a framework for future research in business ethics.